Functional PDMS Elastomers: Bulk Composites, Surface Engineering, and Precision Fabrication - Li, Shaopeng; Zhang, Jiaqi; He, Jian; Liu, Weiping; Wang, YuHuang; Huang, Zhongjie; Pang, Huan; Chen, Yiwang (Advanced science, 2023)
Polydimethylsiloxane (PDMS)—the simplest and most common silicone compound—exemplifies the central characteristics of its class and has attracted tremendous research attention. The development of PDMS‐based materials is a vivid reflection of the modern industry. In recent years, PDMS has stood out as the material of choice for various emerging technologies. The rapid improvement in bulk modification strategies and multifunctional surfaces has enabled a whole new generation of PDMS‐based materials and devices, facilitating, and even transforming enormous applications, including flexible electronics, superwetting surfaces, soft actuators, wearable and implantable sensors, biomedicals, and autonomous robotics. This paper reviews the latest advances in the field of PDMS‐based functional materials, with a focus on the added functionality and their use as programmable materials for smart devices. Recent breakthroughs regarding instant crosslinking and additive manufacturing are featured, and exciting opportunities for future research are highlighted. This review provides a quick entrance to this rapidly evolving field and will help guide the rational design of next‐generation soft materials and devices. Polydimethylsiloxane (PDMS), transforms from the central component in children's toy—silly putty, to the material of choice for many emerging technologies such as flexible electronics, soft actuators, and more, thanks to the advancement in composite science, multifunctional surfaces, and additive manufacturing. This article reviews latest progress in PDMS‐based elastomers and the integrated functionalities, highlighting the opportunities as well as challenges.